2014
DOI: 10.1080/02188791.2014.940031
|View full text |Cite
|
Sign up to set email alerts
|

“We are only looking for the right answers”: the challenges of controversial issue instruction in South Korea

Abstract: This study explores the perceptions of South Korean moral and social studies education teachers, teacher educators, and students on the promises and challenges of introducing and discussing controversial issues within their classrooms. The findings suggest that college entrance exams, textbooks, didacticism, dualism, administrators, textbooks, standards, fear of bias, scant instructional time, and reticent classroom climates collectively undermine controversial instruction in South Korea The few pathways that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…According to the findings, they concluded that the current education system could not meet the needs of students about sexuality and that most of the areas previously identified related to sexuality education were neglected in the curriculum. Misco (2012Misco ( , 2016 in his studies related to curriculum in South Korea claimed that South Koreans were strictly linked to Confucian culture and tradition. This tradition showed itself in textbooks, national curriculum and teacher behaviors that encourage traditional and sovereign beliefs instead of supporting reflective thinking about controversial issues.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings, they concluded that the current education system could not meet the needs of students about sexuality and that most of the areas previously identified related to sexuality education were neglected in the curriculum. Misco (2012Misco ( , 2016 in his studies related to curriculum in South Korea claimed that South Koreans were strictly linked to Confucian culture and tradition. This tradition showed itself in textbooks, national curriculum and teacher behaviors that encourage traditional and sovereign beliefs instead of supporting reflective thinking about controversial issues.…”
Section: Discussionmentioning
confidence: 99%
“…Every society quite naturally makes an effort to preserve their State and pass on their ideologies to future generations. Therefore, talking about impartial education would be an exaggeration (Boyle-Baise, 2010; Misco, 2016). However, if the official ideology indisputably imposes CIs as the only truth, it can bring along polarization and polarized people who in turn will develop their own arguments and desire to pass these on to future generations.…”
Section: Discussionmentioning
confidence: 99%
“…Every society has discussions and CIs (Chikoko et al, 2011;Misco, 2016). Discussing such issues essentially serves the culture of democracy and course objectives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations